Legal Protection of Consumers in Online Buying and Selling Transaction on Sharia E-Commerce - Ade Iskandar Nasution; Oyo Sunaryo Muklas; Burhanuddin Burhanuddin (Jurnal Maps (Manajemen Perbankan Syariah), 2026)
The development of digital technology has brought significant changes to buying and selling patterns, especially with the emergence of sharia e-commerce in Indonesia. Muslim communities are now increasingly choosing e-commerce platforms that offer guarantees for transactions in accordance with sharia principles. However, the growth of sharia e-commerce is also accompanied by challenges and risks, particularly regarding consumer legal protection. Various issues such as fraud, products not matching descriptions, misuse of personal data, and unclear contract terms frequently occur in online transactions. This study aims to analyze the forms of legal protection for consumers in online buying and selling transactions on sharia e-commerce platforms, from both the perspective of national positive law and Islamic legal (sharia) principles. The research adopts a qualitative method with a library research approach, reviewing documents, literature, relevant legislation, and sharia fatwas. The findings indicate that consumer protection in sharia-based online transactions must integrate the principles of justice, honesty, and transparency as contained in the Qur’an and Hadith, and as regulated by the Consumer Protection Act and Electronic Information and Transactions Act (ITE Law). Consumer education, sharia supervisory institutions, and sharia-based dispute resolution mechanisms are key to achieving optimal legal protection. Therefore, integrating national law and sharia principles is crucial to ensure consumer rights and security in Indonesia’s sharia e-commerce ecosystem.